RETRACTED: MiR-221/222 Ameliorates Deoxynivalenol-Induced Apoptosis and Proliferation Inhibition in Intestinal Epithelial Cells by Targeting PTEN - Hou, Lianjie; Tong, Xiong; Lin, Shuyun; Yu, Mingfang; Ye, Wen-Chu; Xie, Meiying (Frontiers in Cell and Developmental Biology, 2021)
Intestinal epithelial cells are critical for nutrient absorption and defending against pathogen infection. Deoxynivalenol (Don), the most common mycotoxins, contaminates cereals and food throughout the world, and causes serious damage to the mammal intestinal mucosa, appears as intestinal epithelial cell apoptosis and proliferation inhibition. Our previous study has found that milk-derived exosome ameliorates Don-induced intestinal damage, but the mechanism is still not fully understood. In this study, we demonstrated that Don down-regulated the expression of miR-221/222 in intestinal epithelial cells, and exosome treatment reversed the inhibitory effect of Don on miR-221/222. Through immunofluorescence and flow cytometry analysis, we identified miR-221/222 ameliorates Don-induced apoptosis and proliferation inhibition in intestinal epithelial cells. Through Bioinformatics analyses and RNA immunoprecipitation analysis, we identified PTEN is the target of miR-221/222. Through the PTEN interfering experiment, we found Don-induced apoptosis and proliferation inhibition relied on PTEN. Finally, through adenovirus to overexpress miR-221/222 in mice intestinal epithelial cells specifically, our results showed that miR-221/222 ameliorated Don-induced apoptosis and proliferation inhibition in intestinal epithelial cells by targeting PTEN. This study not only expands our understanding of how miR-221/222 and host gene PTEN regulate intestinal epithelial cells defending against Don-induced damage, but also provides a new way to protect the development of intestine.